2021
DOI: 10.1017/s0263574720001356
|View full text |Cite
|
Sign up to set email alerts
|

Position-Based Fractional-Order Impedance Control of a 2 DOF Serial Manipulator

Abstract: SUMMARY Impedance control is one of the interaction and force control methods that has been widely applied in the research of robotics. In this paper, a new position-based fractional-order impedance control scheme is proposed and applied to a 2 DOF serial manipulator. An RR robot manipulator with full arm dynamics and its environment were designed using Matlab/Simulink. The position control of the manipulator was utilized based on computed torque control to cancel out the nonlinearities existing on the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…: refs. [16][17][18]). Besides excellent startup response of fractional order controllers (FOCs), some studies also showed that they can work more energy efficiently [19], which makes this control approach more suitable for "off grid" applications (i.e., mobile robots, drones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…: refs. [16][17][18]). Besides excellent startup response of fractional order controllers (FOCs), some studies also showed that they can work more energy efficiently [19], which makes this control approach more suitable for "off grid" applications (i.e., mobile robots, drones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Human-robot cooperative system is a nonlinear time-varying dynamic system with uncertain interference, in which the uncertainty and external interference greatly improve the complexity of the system. Many researchers have designed corresponding controllers for this technical problem, such as variable impedance control method [3], adaptive admittance controller [4], underactuated redundant low impedance method [5], and efficiency weighting strategy [6]. However, the existing methods lack ideal solutions to three main challenges: (1) the control system cannot guarantee the convergence of stable equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The robustness of human-robot cooperative system is endangered by uncertainty and external interference. (3) The nature and characteristics of external interference are difficult to identify and compensate.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the damping term can be defined proportional not to the first-order derivative of the endeffector error, but to a derivative with generic non-integer order µ. In the scientific literature, there are some examples of fractional-order impedance controls of robots [26,27]. This kind of impedance control generalizes to a three-dimensional system the fractional-order PD µ control scheme for SISO systems [28].…”
Section: Introductionmentioning
confidence: 99%